Integrasi Kognitif dan Perilaku dalam Pola Penanaman Disiplin Santri di Pesantren Al- Basyariah Bandung - Hajir Tajiri (AL-TAHRIR, 2011)
The training pattern at a pesantren community has until now been viewed as the best one. The pattern can simultaneously integrate both the cognitive and the behavior of the community. They are not only oriented cognitively by their leaders and teachers but also provided with the environment and living model. This is the case of Pesantren Al-Basyariah Bandung. The school of the Pesantren emphasizes a strict discipline of the day-to-day activities over all members of the community. So, every new members of the community will be informed of a book of discipline rules which also contains the rules of punishments for any offender. The Pesantren applies a tight control over the students, involving all units of the school institution, including student organization (OSPA), and other supporting community outside the school. The cognitive-behavior pattern of training has been proved effective at Pesantren AlBasyariah as a model of training.